EVALUATION OF ENGINEERING PROPERTIES OF THERMAL POWER PLANT WASTE FOR SUBGRADE TREATMENT - Hossain, Md. Belal; Roknuzzaman, Md.; Biswas, Md. Asib; Islam, Motaharul (Journal of Civil Engineering, Science and Technology, 2021)
Soft cohesive soils have low strength, high plasticity, and a large expansion ratio making them unsuitable as a road subgrade. This study aims to evaluate the potential of power plant waste (fly ash) from the Barapukuria Thermal Power Plant, Dinajpur, Bangladesh to improve the characteristics of such soft cohesive soil. X-ray fluorescence test conducted to classify the power plant fly ash and the type was identified as “Class F” according to “American Association of State Highway and Transportation Officials” and "American Society for Testing and Materials". Laboratory tests were conducted on clay soil obtained from Dinajpur region modified by the collected power plant waste. As the Class F fly ash has low cementing property, 3% cement was added with it. Cement mixed soil was modified with 5%, 10%, 15%, and 20% fly ash respectively. Specific Gravity, Atterberg limits, Modified Proctor Compaction, Unconfined Compressive Strength (UCS) and California Bearing Ratio (CBR) tests were conducted. The study reveals that there is a decrease in specific gravity, dry density, and plasticity index with the addition of power plant waste. On the other hand, there is an increase in optimum moisture content, UCS, and CBR value. UCS and CBR values were found to be improved remarkably. Soaked CBR value of soil is found to be improved from 2.79% to 92.59% when treated with 5% fly ash and 3% cement. The UCS value of this modified soil was 560.36 kPa. The stabilized soil thus obtained meets the requirements for subgrade as specified by the Local Government Engineering Department (LGED)’s design manual (2005), Bangladesh. Since there is a possibility of leaching by dumping a large quantity of fly ash in the pond, the use of fly ash from the power plants to improve soft cohesive soils for road subgrade may be an environment-friendly alternative to its disposal in the ponds.